Pelatihan Model dan Media Pembelajaran Inovatif pada Kurikulum Merdeka - Irmaningrum, Rizka Novi; Zativalen, Oriza; Nurhidayat, M Arif (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
The purpose of implementing this training is to produce quality teachers by carrying out training activities on models and learning media in the independent curriculum at SD Muhammadiyah 1 Babat. It is hoped that this training activity can provide knowledge and information to teachers to improve the quality of teaching in the independent curriculum by implementing innovative learning models and media. This makes teachers able to understand innovative learning models for the independent curriculum, able to apply innovative learning models for the independent curriculum, able to understand innovative learning media for the independent curriculum, and able to apply innovative learning media for the independent curriculum. This is a solution to various kinds of learning problems in the independent curriculum. The training targets who will be involved in this activity are all teachers at SD Muhammadiyah 1 Babat. The method that will be used is the training planning stage for grade 1 and 4 teachers by preparing independent curriculum analysis, innovative learning models and media. The second stage is the implementation of training on innovative learning models and media in the independent curriculum. The third stage is evaluation and follow-up to differentiate the results of the pretest and posttest. said to be successful and considered good. The results of community service that have been carried out, namely the success of implementing community service activities, apart from being measured from the components above, can also be seen from participant satisfaction after participating in training activities. The school is very satisfied with the activities provided by the service team because they provide significant benefits, including: increasing knowledge about innovative learning models and media for the Merdeka curriculum. Conclusion: The implementation of community service activities has been carried out well and teachers are able to create innovative learning models and media. The service material is model training and learning media for the independent curriculum at SD Muhammadiyah 1 Babat. Follow up by providing regular monitoring of the implementation of the use of learning models and media. The final stage is publishing scientific work on community service.